Can parents protect their children? Risk comparison analysis between affiliates of multi- and single-bank holding companies - Ly, Kim Cuong; Liu, Frank Hong; Opong, Kwaku (Journal of Financial Stability, 2018)
We find that multi-bank holding companies (MBHCs) in the U.S. have lower insolvency risk than single-bank holding companies (SBHCs) at the parent level, but have significantly higher insolvency risk than the latter at the subsidiary level. Our results suggest that MBHC parents tend to benefit from the internal capital market while allowing for more risk-taking at the individual levels. We further find that the higher risk for MBHC affiliates is because of the organizational and geographic complexity at the MBHC parent level. Our results highlight the importance of government regulation on banks at both parent and subsidiary levels.